Earnings Management in Response to the Introduction of Additional Corporate Income Tax - Šušak, Toni (Ekonomika, 2026)
The objective of this research was to assess the impact of the introduction of windfall taxes on accrual earnings management in the Republic of Croatia. The Croatian windfall taxation setting was unique in the European Union due to the comprehensive taxpayer approach. The research sample included 115 companies eligible for windfall tax treatment in the Republic of Croatia in the time period from 2020 to 2023. Panel regression analysis was used to estimate the model necessary for hypothesis acceptance, and the Modified Jones model was utilized to calculate the magnitude of discretionary accruals as a proxy of earnings management. The research findings showed a positive relationship between absolute discretionary accruals and additional corporate income tax liabilities for the companies that utilized downward earnings management, which indicates the presence of a tax minimization issue through accrual earnings management during the period of windfall taxation. This research has practical implications for the legislature, tax authorities, and other users of financial statements and academia. Tax authorities and other users of financial statements may exercise caution in interpreting the financial information of companies eligible for windfall taxation. To prevent accounting manipulations, regulators should consider taking measures such as establishing a windfall taxation scheme based on the profitability of an industry or demanding more frequent disclosure of financial information from potential windfall taxpayers.